Pengaruh Kualitas Produk, Persepsi Harga dan Citra Merek terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan - Septianingrum, Salsabiil Helga; Triyono, Triyono; Fajri, Annisa (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
Instant noodles are classified as fast food and have become a staple food. There are many brands of instant noodle products on the market. This creates increasingly fierce business competition and forces business people to compete competitively. Thus, this study aims to examine the effect of product quality, price perception, and brand image on customer loyalty of instant noodle products through customer satisfaction. The object of research were 88 students of the Faculty of Economics, University of Muhammadiyah Semarang, Study Program of Management and Accounting. This study explains that the sales level of the instant noodle market has increased as indicated by the number of customers who have loyalty to consume fast food. To maintain its position, instant noodle companies strive to maintain and maximize product quality, price perception and brand image strategies through customer satisfaction. The results showed that product quality and price perceptions did not have a positive and significant effect on customer loyalty, but instant noodle products must maintain brand image, customer satisfaction and improve other factors that have the potential to increase customer loyalty.